Joh. Amos Commenii Orbis sensualium pictus: hoc est, omnium fundamentalium in mundo rerum, & in vita actionum, pictura & nomenclatura. Joh. Amos Commenius's Visible world: or, a picture and nomenclature of all the chief things that are in the world; and of mens employments therein. / Written by the author in Latin and High-Dutch (being one of his last essays, and the most suitable to childrens capacities of any that he hath hitherto made) and translated into English, by Charles Hoole, M.A. for the use of young Latin-scholars. [electronic resource] = (1689)
Summary goes here